Beryllium bonding with noble gas atoms. Issue 4 (17th November 2022) - Mazumder, Lakhya Jyoti; Sharma, Rohan; Yashmin, Farnaz; Sharma, Pankaz Kumar
Abstract: Quantum chemical calculations were carried out to investigate the nature of the bonding between a neutral Be3 ring and noble gas atom. Electronic structure calculation for these complexes was carried out at different computational levels in association with natural bond orbital, quantum theory of atoms in molecules, electron localization function, symmetry adapted perturbation theory, and molecular electrostatic potential surface analysis of Be3 complexes. The Be atoms in the Be3 moiety are chemically bonded to one another, with the BeBe bond dissociation energy being ~125 kJ mol −1 . The Be3 ring interacts with the noble gases through non‐covalent interactions. The binding energies of the noble gas atoms with the Be3 ring increases with increase in their atomic number. The non‐covalent interaction index, density overlap region indicator and independent gradient model analyses reveal the presence of non‐covalent inter‐fragment interactions in the complexes. Energy decomposition analysis reveals that dispersion plays the major role towards stabilizing these systems. Abstract : Quantum chemical calculations predict the presence of inter‐fragment non‐covalent interactions between Be3 ring and noble gas atoms in Ng@Be3 and Ng2 @Be3 complexes.